Upaya meningkatkan kepedulian peserta didik terhadap keberlangsungan lingkungan - Maresi, Sinta Ramadhania Putri; Basoeki, Agastyo Djanardono (Institute for Advanced Science, Social, and Sustainable Future, 2024)
In Indonesia, Education purposes of developing students’ potency to be religious, moral, healthy, competent, creative, and independent people and to be democratic and responsible societies. Related to environmental issues, schools should educate their students to be healthy and have responsibilities to their environmental condition. This is because healthy schools can improve students’ life expectancy then they can optimally study, grow, and develop to be capable people. Following this explanation, schools should integrate environmental education with their curriculum. Environmental education is also part of government efforts to increase students’ environmental knowledge to improve their environmental care behaviour and to reduce environmental degradation. This is based on the small degree of environmental care students behaviour in Indonesia, although the government has been many efforts to improve it. Therefore, the knowledge of the correlation between students and environmental issues and approach to improve students’ environmental care should be realized. This can be applied with a qualitative approach and method with literature study and documentation of previous researches and environmental theories as data collection techniques. This research also applies an interactive method, including data reduction, data presentation, and concluding, as data analyses technique. As a result, there is a significant correlation between students’ educational background and students’ environmental care behaviour. However, students’ contribution to environmental knowledge and environmental care is in a low position. Furthermore, schools should integrate environmental literacy and educational curriculum. If schools can apply this curriculum model continually, then students’ environmental knowledge and care can be improved and will effect on environmental sustainability positively.